03 The Effects of Using Viber on Iranian EFL University Students' Vocabulary Learning (An Interactionist View) - Fahimeh FARAHMAND; Mohammad Ali KOWSARY (Association of Social and Educational Innovation, 2016)
One of the best ways of learning English is using technology. Actually mobile phone plays the key role in learning English. Today, there are many applications are used for learning and teaching English. Viber is an instant messaging and Voice over IP (VoIP) application for smart phones developed by Viber Media. In addition to instant messaging, users can exchange images, video and audio media messages. Viber is a new software which is used for many purposes. Viber users communicate with each other through textual and oral messages. The aim of this study is to elaborate the exact relationship between using Viber and improvement of vocabualry knowledge. The researchers have chosen 15 male and female EFL University Students which were weak in vocabulary domain at first. Participants were gathered in a Viber group and communicate with each other under the professor's control. After one month, the results declared that there is a meaningful relationship between using Viber and Students' Vocabulary Learning. The results also showed that learners were more interested in learning English through Viber.